Conceptualizing a Genomics Software Institute (GSI). Issue 1 (January 2012) - Gilbert, Jack; Catlett, Charlie; Desai, Narayan; Knight, Rob; White, Owen; Robbins, Robert; Sankaran, Rajesh; Sansone, Susanna-Assunta; Field, Dawn; Meyer, Folker
Abstract Microbial ecology has been enhanced greatly by the ongoing 'omics revolution, bringing half the world's biomass and most of its biodiversity into analytical view for the first time; indeed, it feels almost like the invention of the microscope and the discovery of the new world at the same time. With major microbial ecology research efforts accumulating prodigious quantities of sequence, protein, and metabolite data, we are now poised to address environmental microbial research at macro scales, and to begin to characterize and understand the dimensions of microbial biodiversity on the planet. What is currently impeding progress is the need for a framework within which the research community can develop, exchange and discuss predictive ecosystem models that describe the biodiversity and functional interactions. Such a framework must encompass data and metadata transparency and interoperation; data and results validation, curation, and search; application programming interfaces for modeling and analysis tools; and human and technical processes and services necessary to ensure broad adoption. Here we discuss the need for focused community interaction to augment and deepen established community efforts, beginning with the Genomic Standards Consortium (GSC), to create a science-driven strategic plan for a Genomic Software Institute (GSI).